Types of Fathers’ Home-based and School-based Involvement in a Hungarian Interview Study - Csák, Zsolt (Central European Journal of Educational Research, 2023)
This study explores the ways that Hungarian fathers are involved, at home and at school, in their children’sdevelopment and achievement. It also identifies the types of fathers that emerge based on this involvement.According to the literature, paternal involvement at home and at school contributes to academic achievement,similar to the involvement of mothers, but to a lesser extent and in different ways. The theoretical framework ofthe research relies on the types of parental involvement as defined by Epstein. The research was qualitative,based on 14 semi-structured interviews and the classification of fathers, resulting in three groups of similar size.The first group comprised fathers who contributed to their child’s achievement at home, often by helping withschool-related activities, while not participating in school events. The second group included fathers who wereinvolved at home and at school alike. Finally, the third group consisted of four divorced fathers, three of whomwere involved both at home and at school, due to their particular situation. Overall, fathers’ school-basedinvolvement can be increased by the supportive attitude of wives, fathers’ greater confidence in themselves andtheir abilities, and by informal events organized by schools (cooking or sports days), in which fathers are morelikely to participate.